PASSIVATION OF THERMAL CRACKING FURNACE CONDUIT - HAYNAL, ROBERT, J; WEBBER, KENNETH, M; MASON, ROBERT, W (2011)
A method for passivating at least part of the feed conducting conduit of a pyrolysis furnace to reduce the deposition of coke in that conduit, the passivation being accomplished by employing at least one phosphorous containing compound. Cette invention concerne un procédé de passivation d'au moins une partie du conduit acheminant la charge d'un four à pyrolyse pour réduire le dépôt de coke dans ce conduit, la passivation étant effectuée en employant au moins un composé phosphoré.